REPRESENTASI PERLAWANAN TOKOH GURU PEREMPUAN DALAM FILM “BRAVE CITIZEN” - Arilaha, Najla Arinka; Burhan, Amelia (Multikultura, 2026)
Representation of women in literary works, including film, are often shaped by gendered constructions that limit their agency, including within the teaching profession in South Korea. Brave Citizen represents this dynamic through the character So Simin and provides a lens to examine how women are represented when confronting gender inequality and hierarchical structures within the school environment. This study aims to explain how the film Brave Citizen depicts women’s resistance through a female teacher character focusing on challenging gender stereotypes in educational settings. Employing a descriptive qualitative method and Barthes’ semiotic analysis, this research identifies denotative, connotative, and mythical meanings in key scenes, further supported by Bem’s Sex Role Inventory (BSRI) to assess the configuration of feminine and masculine traits in the main character. The findings reveal three stages of So Simin’s resistance, such as women’s powerlessness, symbolic resistance, and physical resistance and identity reconstruction. These findings demonstrate that the integration of feminine and masculine traits forms a functionally androgynous identity, enabling So Simin to negotiate her position and agency within a hierarchical school structure marked by gender bias.